Assessing potential health risk of heavy metal exposure in instantly foods commonly consumed in Selangor, Malaysia / Hanim Akilah Adnan - Adnan, Hanim Akilah (2015)
Food are the main sources of toxic elements intake for humans and have detrimental effects on various metabolic processes if they are present in relatively high concentrations. Heavy metal is mainly the result of human activities such as agriculture, mining, construction and industrial processes. Heavy metals are individual metals and metals compounds that can give impact to human health, and generally human are exposed to the heavy metals by ingestion or inhalation. Metals are divided into two categories namely hazardous and non-hazardous group. The main objective of this study is to determine the concentration of heavy metals in peanuts, rice and anchovies and to assess the potential health risks associated with heavy metals due to intake of these types of staple food. The parameters which cadmium (Cd), copper (Cu) iron (Fe), lead (Pb), and zinc (Zn) were conducted on rice, peanuts and anchovies. This research is a cross sectional study. The sample has been randomly collected by purchased them from different retail shops in three different cities in Selangor province including Puncak Alam, Shah Alam, and Meru. All the samples were collected to be analyzed. The analysis for heavy metal were performed on a heated furnace-atomic absorption spectrometer (FAAS). Then all the data and results were analyzed using Statistical Package Social Science. The results shown that there were significant differences on the concentration presents in the rice, peanuts and anchovies for the heavy metals for Cd, Cu, Fe, Pb and Zn since the p values is < 0.005. It was found that the mean concentration in rice and peanuts samples decreased from Zn> Fe> Pb > Cu> Cd. While the mean concentration in anchovies samples decreased from Fe > Pb > Zn > Cu > Cd. Target Hazard Quotient of heavy metal (Zn, Pb, Cu, Cd, Fe) was calculated to estimate the potential health risk to consumer. Health Risk Assessment indicates -that rice, peanuts and anchovies are not safe for consumption regarding to its hazard index is greater than 1 for Cd, and Pb. As a conclusion, all samples analyzed in this study are poses potential health risk in future. Therefore, further assessment of heavy metals in staple foods from the contaminated sources is necessary.